Teaching and Learning Strategies - Baxtiyor qizi, Dushatova Shohsanam; Erkijon qizi, Sobirjonova Feruza (Academia Open, 2022)
This scientific article examines the effectiveness of creativity and language learning strategies in foreign language teaching and the advancement of speaking, writing, reading, and listening comprehension skills. By employing multimedia resources such as videos, audios, and songs, the study aims to investigate the impact of these tools on language acquisition. Through a comprehensive analysis of various methodologies, the research reveals that integrating multimedia into language learning fosters a more engaging and immersive environment, leading to significant improvements in learners' linguistic abilities. The findings suggest that incorporating creativity and language learning strategies through multimedia can facilitate more efficient language acquisition and provide valuable implications for foreign language education practices. Highlights: Multimedia integration enhances language acquisition: The study demonstrates the positive impact of multimedia resources, such as videos, audios, and songs, on the development of speaking, writing, reading, and listening comprehension skills in foreign language learners. Creativity and language learning strategies promote engagement: The research highlights the importance of incorporating creative approaches and effective language learning strategies in foreign language teaching to create an immersive and stimulating learning environment. Implications for foreign language education practices: The findings provide valuable insights for educators, suggesting the integration of multimedia and the utilization of creativity and language learning strategies to enhance language acquisition and improve overall linguistic abilities in learners. Keywords: creativity, language learning strategies, multimedia integration, foreign language teaching, linguistic abilities.